A Study on The Healthy Rental-Housing for College Students According to World Health Organization: Evidence from Surabaya City in Indonesia - Rahayu, Ardiani Putri; Abidin, Sharilla Aryananti; Islami, Afifah Faradilla; Ruslan, M. Syafiq Hazlan; Kurnia, Kiki Adi (Journal of Public Health for Tropical and Coastal Region, 2021)
Introduction:Many college students live far from their parents to study to get a better higher education, so they occupy a rental-housing. However,many rental-housings do not meet the health standards according to the World Health Organization (WHO). Therefore, this study aiming at evaluating the rental-housing quality used by college students in Surabaya, Jawa Timur, Indonesia.Methods:This type of research is an observational study conducted with a descriptive observational design. The sample in this study was 52 college students who originated from outside Surabaya and currently living in the rental-housing in Mulyorejo, Surabaya, Indonesia.Results:The results present observational data from 52 student respondents who live in boarding houses including the overview of boarding houses condition, ventilation and air circulation condition, trash management, clean water and wastewater management, and toilet condition.Conclusion: Under the circumstance, this study was conducted to assess healthy rental-housing quality for college students, using the WHO's evaluation indicators. While some college students could afford to stay in proper and healthy rental-housing, some of them still suffer from lousy ventilation, the absence of clean water, and terrible trash management.